Digital Financial Use and Its Effects on Household Economic Decisions Derived from the Statistics Indonesia Socioeconomic Data - Nunung Wulan Sari (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background:The rapid proliferation of digital financial services in Indonesia has dramatically transformed household economic behavior. However, a comprehensive understanding of these effects across diverse socioeconomic contexts remains limited.Objective:The objective of this study is to examine the effects of digital financial services on household economic decisions, utilizing socioeconomic data from Badan Pusat Statistik (Statistics Indonesia). The study aims to assess how digital finance adoption influences consumption expenditure, savings, risk management, and access to formal credit.Method:The study employs a quantitative research design, analyzing data from 500 households.Findings and Implications:Digital finance adoption increases household consumption by 18.6%, raises savings rates by 4.8 percentage points, and boosts formal savings account ownership by 32.4%. Users also demonstrate stronger risk management, with 64.8% maintaining adequate emergency funds (compared to 38.6% of non-users), and enjoy higher formal credit approval rates of 72.6%. The greatest benefits are observed among urban, educated, and middle-income households. These results offer valuable insights for policymakers to optimize digital financial inclusion strategies, emphasizing the need for complementary interventions to address infrastructure gaps, improve financial literacy, and strengthen consumer protection.Conclusion:The study underscores the importance of digital financial services in shaping household economic decisions and highlights the need for targeted interventions to ensure equitable access across diverse socioeconomic groups. Policymakers should focus on enhancing infrastructure, financial literacy, and consumer protection mechanisms to maximize the benefits of digital financial inclusion for all segments of the population.